Protein landscape of the brush border membrane of first instar larvae of Frankliniella occidentalis, the western flower thrips. - Marlonni Maurastoni; Dorith Rotenberg; Ruchir Mishra; Bryony C Bonning; Anna E Whitfield (PLoS ONE, 2025)
We investigated the protein composition of the brush border membrane of larval Frankliniella occidentalis (western flower thrips), an agriculturally significant crop pest and vector of plant pathogens. We developed a protocol for purifying brush border membrane vesicles (BBMVs) from first-instar larvae (L1) bodies and identified their protein composition by LC-MS/MS. From 2544 proteins identified, 469 were predicted to be secreted and part of the inner and outer plasma membrane leaflet using cell-localization prediction tools and homology with reviewed proteins in the UniProt database. Comparison to thrips tissue-specific proteomes revealed that 371 and 263 of the identified BBMV plasma membrane and secreted proteins matched the larval gut and adult salivary glands, respectively. Annotations of most of the proteins inferred 'catalytic activity' (56.3%) and 'binding' (49.6%), with an overrepresentation of proteins involved in protein digestion, specifically serine proteases, lipid transport, and ATPase activity. Bioinformatic-enabled comparisons to thrips tissue-specific proteomes and transcriptomes enabled us to predict the secretome and the plasma membrane proteins of larval thrips' gut epithelial cells, providing new targets for thrips control.